Time, frequency, and quantile-based impacts of disaggregated electricity generation on carbon neutrality: evidence from leading European Union countries - Kartal, Mustafa Tevfik; Pata, Ugur Korkut; Depren, Serpil Kilic; Erdogan, Sinan (TAYLOR & FRANCIS INC, 2024)
Due to increasing geopolitical tensions and disruption of gas supplies, European countries have been looking for alternatives for electricity generation (EG). As part of this process, one of the most important goals for long-term sustainability is to ensure carbon neutrality. Therefore, this study analyzes time, frequency, and quantile-based impacts of EG from different electricity generation sources (i.e., renewable, nuclear, and fossil fuels) on carbon neutrality, focusing on four leading European countries. The study applies the wavelet transform coherence (WC), quantile-on-quantile regression (QQ), and Granger causality in quantiles (GQ) to high-frequency daily data between January 2, 2019 and March 10, 2023. Results show that (i) there is a strong time and frequency dependence between EG and CO2 emissions across countries, while results vary by EG sources and countries; (ii) renewable EG dampens CO2 emissions. At higher quantiles, a higher share of renewable EG lowers CO2 emissions in Germany and Spain, while they increase in France; (iii) nuclear EG is beneficial only for the United Kingdom. (iv) Fossil EG increases CO2 emissions in all countries. Excessive fossil EG leads to more CO2 emissions at higher quantiles; (v) the impacts of EG on CO2 emissions have a time-, frequency, quantile-, country-, and EG source-dependent structure. The outcomes of the study demonstrates that the ideal EG source for countries is mainly renewable EG, while in the case of the United Kingdom, nuclear EG could be an alternative for improving the environment while reducing fossil fuels.
Keywords: Electricity; CO2 emissions; European Union countries; Disaggregated Analysis; nonlinear methods; ENVIRONMENTAL KUZNETS CURVE; RENEWABLE ENERGY-CONSUMPTION; MITIGATING CO2 EMISSIONS; ECONOMIC-GROWTH; NUCLEAR-ENERGY; FINANCIAL DEVELOPMENT; EKC HYPOTHESIS; FOSSIL; PANEL; URBANIZATION; Science & Technology - Other Topics; Environmental Sciences & Ecology